2020
DOI: 10.1103/physrevb.101.064425
|View full text |Cite
|
Sign up to set email alerts
|

Direct control of magnetic chirality in NdMn2O5 by external electric field

Abstract: Detailed investigation of the incommensurate magnetic ordering in a single crystal of multiferroic NdMn2O5 has been performed using both non-polarized and polarized neutron diffraction techniques. Below TN ≈ 30.5 K magnetic Bragg reflections corresponding to the nonchiral type magnetic structure with propagation vector k1 = (0.5 0 kz1) occurs. Below about 27 K a new distorted magnetic modulation with a similar vector kz2 occurs, which is attributed to the magnetization of the Nd 3+ ions by the Mn-sub-lattice. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The reported XRD patterns allow us only to calculate the c-lattice constants. However, previous crystallographic studies carried out on our samples [16,19,24] have identified an orthorhombic structure with the Pbam space-group symmetry. The reported lattice constants a, b, and c are found to be 7.4940, 8.6071, and 5.6934 Å for NdMn 2 O 5 (at 300 K); 7.531(5), 8.610(5), and 5.719(5) Å for Nd 0.8 Tb 0.2 Mn 2 O 5 (at 3.8 K); and 7.351, 8.60, and 5.690 Å for TbMn 2 O 5 (at 300 K), respectively.…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…The reported XRD patterns allow us only to calculate the c-lattice constants. However, previous crystallographic studies carried out on our samples [16,19,24] have identified an orthorhombic structure with the Pbam space-group symmetry. The reported lattice constants a, b, and c are found to be 7.4940, 8.6071, and 5.6934 Å for NdMn 2 O 5 (at 300 K); 7.531(5), 8.610(5), and 5.719(5) Å for Nd 0.8 Tb 0.2 Mn 2 O 5 (at 3.8 K); and 7.351, 8.60, and 5.690 Å for TbMn 2 O 5 (at 300 K), respectively.…”
Section: Methodsmentioning
confidence: 63%
“…Furthermore, its electrical polarization develops at T 2 ∼ 26 ± 2 K (T C ), arises only in an incommensurate state, being in contrast with other RMn 2 O 5 multiferroic members [11]. These properties render NdMn 2 O 5 unique as a reference member of the RMn 2 O 5 series to provide a deeper understanding of the fundamental mechanisms behind its magnetic and electric properties [15][16][17][18]. Doping this parent compound with smaller rare-earth elements, such as terbium (Tb), could enhance its multiferroic character.…”
Section: Introductionmentioning
confidence: 99%